Some algorithmic aspects of subspace identification with inputs - Chiuso, Alessandro; Picci, Giorgio (Zielona Góra: Uniwersytet Zielonogórski)
It has been experimentally verified that most commonly used subspace methods for identification of linear state-space systems with exogenous inputs may, in certain experimental conditions, run into ill-conditioning and lead to ambiguous results. An analysis of the critical situations has lead us to propose a new algorithmic structure which could be used either to test difficult cases and/or to implement a suitable combination of new and old algorithms presented in the literature to help fixing the problem.
Keywords: subspace identification; multivariable systems; identification with inputs; ill-conditioning